Cultivation of Spirulina using rainwater as an alternative nutrient source - Manivannan, Hushwinie (Nanyang Technological University, 2024)
Arthrospira platensis, known as Spirulina, is a blue-green microalga with high nutritional value. Traditionally cultivated in nutrient-rich synthetic media, Spirulina uses a significant amount of water for cultivation. Despite research on alternative water sources, low yields and the possibility of contamination have made it unsuitable for cultivation. This study will therefore assess the usage of rainwater as an alternative to conventional water sources in the growth media, along with an analysis of microfiltration and UV exposure as pre-treatment measures to eliminate contaminants from the media. The biomass productivity of Spirulina in traditional media will be compared with that of four different cultures. These cultures will vary in the amount of nutrients added—either half or full nutrient—and in the treatment of the rainwater. Results showed that the treated media supplemented with half nutrients had an average of 17.55% greater growth than the culture in traditional media. The treatments also successfully removed external contaminants from the media, as seen by the increased biomass productivity of the treated media. These results therefore suggest that rainwater can replace traditional media in cultivation of Spirulina.